Unilateral thalamic edema in internal cerebral venous thrombosis: is it mostly left? - Küker, W; Schmidt, F; Friese, S; Block, F; Weller, M (2001)
Thrombotic occlusion of the internal cerebral veins is a particularly dangerous form of cerebral venous thrombosis (CVT) as it causes venous infarction of the thalami. Because both thalami drain into the vein of Galen and straight sinus, bilateral thalamic involvement is frequently encountered in internal CVT. However, unilateral thalamic edema may also occur, even if all internal cerebral veins are occluded. This suggests collateral venous drainage of the thalami, which is commonly insufficient in internal CVT. Patients with unilateral congestion of the thalamus, including 3 patients reported here, had mostly left-sided involvement, indicating that right-sided unilateral thalamic involvement in CVT may be clinically silent.